2008
DOI: 10.1021/bi7023783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protein Oxidation on the Structure and Stability of Model Discoidal High-Density Lipoproteins

Abstract: High-density lipoproteins (HDLs) prevent atherosclerosis by removing cholesterol from macrophages and by providing anti-oxidants for low-density lipoproteins. Oxidation of HDLs affects their functions via the complex mechanisms that involve multiple protein and lipid modifications. To differentiate between the roles of oxidative modifications in HDL proteins and lipids, we analyzed the effects of selective protein oxidation by hypochlorite (HOCl) on the structure, stability and remodeling of discoidal HDLs rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 50 publications
4
29
1
Order By: Relevance
“…Less salt-bridges pair the protein strands in the spherical HDL particle than in the discoidal HDL particle, the latter exhibiting about 18 salt-bridges (as measured from all-atom simulations of discoidal HDL reported in Shih et al (2005)). Apparently, breakage of salt-bridges is necessary during maturation of HDL, which is consistent with observations that oxidation of HDL particles leads to enhanced conversion of discoidal to spherical HDL (Jayaraman et al, 2008). In Catte et al (2008), all-atom simulations of smaller spherical HDL particles were reported to contain between 10 and 12 salt-bridges.…”
Section: Resultssupporting
confidence: 90%
“…Less salt-bridges pair the protein strands in the spherical HDL particle than in the discoidal HDL particle, the latter exhibiting about 18 salt-bridges (as measured from all-atom simulations of discoidal HDL reported in Shih et al (2005)). Apparently, breakage of salt-bridges is necessary during maturation of HDL, which is consistent with observations that oxidation of HDL particles leads to enhanced conversion of discoidal to spherical HDL (Jayaraman et al, 2008). In Catte et al (2008), all-atom simulations of smaller spherical HDL particles were reported to contain between 10 and 12 salt-bridges.…”
Section: Resultssupporting
confidence: 90%
“…Few studies investigated the influence of HOCl-treatment on protein activity, and only a very select number of investigations dealt with the potential influence of low concentrations of HOCl on the folding status of proteins (Hawkins and Davies, 2005; Jayaraman et al, 2008). Our results indicated that low HOCl to protein ratios cause the unfolding of Hsp33 in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Oxidized proteins have often been reported to have reduced bioactivity, [30][31][32][33] to play a role in several diseases [34][35][36][37] and to influence protein aggregation and conformation. 38,39 It has also been reported that oxidation can create problems during downstream processing. 40 In these studies, obtaining large quantities of naturally oxidized proteins can be an issue.…”
Section: Discussionmentioning
confidence: 99%